Effect of acrylamide on glucose homeostasis in female rats and its mechanisms. (January 2020) - Yue, Zonghao; Chen, Yanjuan; Song, Yujuan; Zhang, Jie; Yang, Xingdong; Wang, Jian; Li, Lili; Sun, Zhongke
Abstract: Acrylamide (AA), a food contaminant, caused islet remodeling and increased hepatic glycogen content in male rats, but the effect of AA on glucose homeostasis in female rats remains unclear. In this study, female SD rats were orally treated with 0, 15, or 30 mg/kg·bw AA for 3 weeks. The levels of fasting blood glucose (FBG), blood glucose after oral administration of glucose, plasma insulin and hepatic glycogen were measured. The histology of the pancreas was observed, and the transcription of key genes involved in glucose metabolism and insulin signaling in liver were determined. Compared with the control, exposure to 30 mg/kg·bw of AA significantly increased FBG level, reduced hepatic glycogen content and impaired glucose tolerance. Moreover, damaged islets were observed at 15 and 30 mg/kg·bw AA-exposed groups. In addition, AA exposure significantly promoted gluconeogenesis and glycogenolysis (up-regulation of pc, g6p and gp ) and decreased glycolysis (down-regulation of gck and pfk ). Alternations in these processes may be associated with decreased plasma insulin levels and inhibited insulin-regulated IRS/PI3K/Akt/Foxo1 signaling transduction under AA exposure. Overall, our findings demonstrated that AA disrupted glucose homeostasis and elevated FBG level in female rats possibly by interfering with glucose metabolism and hampering the physiological effect of insulin. Highlights: Acrylamide (AA) elevated FBG levels and impaired glucose tolerance in female rats. AA decreased insulin levels and hepatic glycogen contents, and damaged pancreatic islets in female rats. Related genes involved in glucose metabolism and insulin signal transduction contribute to AA-induced hyperglycemia.